Stress and Coping Strategies among Nursing Students of selected Nursing College of Kathmandu - Dhakal, Amrita; Dhakal, Muna; Gurung, Varsha (Journal of Karnali Academy of Health Sciences, 2025)
Background: As nursing students have to work in different wards and deal with different types of patients, the dynamic clinical and academic environment makes them continuously exposed to the stressful situations. The purpose of the study was to identify stress and coping strategies among nursing students of Kathmandu. Methods: A cross-sectional research design was used. Simple random sampling technique was used to choose 130 students. The tool Perceived Stress Scale and Cope Behavior Inventory was adopted for collection of data. Descriptive and Inferential statistics were used for analysis. For measurement of relationship correlation test was used. Results: Every nursing student perceived stress. The overall stress perceived by the students was 1.8±0.75. Stress from assignment (M= 2.41± 0.80) was identified as the most frequent cause of stress. Problem solving (M= 2.44 ± 0.90) was the most common coping strategy adopted. A positive relationship was established between the stress scale and subscales of coping strategies (r = 0.183, p< 0.05). Conclusions: This study shows every nursing student experiences some degree of stress during their study period. So effective counselling programs need to be arranged to help them to utilize the positive coping strategies like problem solving and staying optimistic when dealing with the stress.